Phytochemical Investigation, Isolation and Characterization of Coumarins from Aerial Parts and Roots of Tunisian Pituranthos chloranthus (Apiaceae) - Aloui, Latifa; Kossentini, Mohamed; Geffroy-Rodier, Claude; Guillard, Jérôme; Zouari, Sami (Pharmacognosy Communications)
Pituranthos chloranthus, commonly known in Arabic as ‘Aljen,’ is a small aromatic plant which grows spontaneously in North Africa and it is widespread in central and southern Tunisia. This paper is the first report of its kind on the isolation and characterization of certain coumarin derivatives from the extract of the roots and aerial parts of this plant. Background: Pituranthos chloranthus (Apiaceae) commonly known as ‘Aljen’ is an endemic Tunisian aromatic plant, largely used in folk medicine. This plant contains bioactive compounds, particularly coumarin derivatives. The objective of the present study was to isolate and characterize some bioactive phytochemical constituents from the extract of the aerial parts and roots of Pituranthos chloranthus. Methods: Different extracts were subjected to column chromatography and eluted with solvent mixtures of increasing polarity (petroleum ether, ethyl acetate and methanol) to isolate five pure Products. The structure of the isolated compound was established using spectroscopic methods (UV, 1 H-NMR, 13C-NMR, DEPT, HMBC, HSQC, COSY), and HRMS. Results: Isoimperatorin, osthol and oxypeucedanin were isolated from the n-hexane and ethyl acetate extract of the aerial part of the plant. Bergapten and nodakenetin were isolated from the methanolic extract of the roots. Conclusion: Pituranthos chloranthus contains bergapten, isoimperatorin, nodakenetin, osthol and oxypeucedanin which may be responsible for various pharmacological activities of the plant.
Keywords: Apiaceae; Bioactive compounds; oxypeucedanin; Pituranthos chloranthus